2011
DOI: 10.4172/2155-6199.1000132
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Molecular and Biochemical Identification of Paraoxon-Metabolizing Pseudomonas Species

Abstract: Seven soil borne bacterial isolates were collected from locations throughout the Houston metropolitan area. All isolates proved capable of degrading the pesticide paraoxon to p-nitrophenol in carbon limited media and showed a high degree of tolerance to an environment exposed to increasing concentrations of the pesticide. A combination of 16S rRNA sequencing and fatty acid methyl ester (FAME) analysis was used to identify the unknown bacterial species. Universal bacterial primers were used for 16S rRNA analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Equal volumes of acetonitrile and culture supernatant were mixed, and then the mixture Malathion degrading gene of the selected bacterial strain was detected by the presence of organophosphorus hydrolase encode as (opd) gene using specific primers, forward primer (opd F169) sequence is 5'CGCGGTCCTATCACAATCTC3' and reverse primer (opd R169) sequence is 5'CTTCTAGACCAATCGCACTG3' [33] with using1.5 μl of standard 1kb DNA ladder (Thermo Scientific, USA) were loaded in 1% agarose gel. Digital images were obtained for PCR products bands using Bio-Rad's Gel Doc XR+ system.…”
Section: Malathion Residual Analysis Using High-performance Liquid Ch...mentioning
confidence: 99%
“…Equal volumes of acetonitrile and culture supernatant were mixed, and then the mixture Malathion degrading gene of the selected bacterial strain was detected by the presence of organophosphorus hydrolase encode as (opd) gene using specific primers, forward primer (opd F169) sequence is 5'CGCGGTCCTATCACAATCTC3' and reverse primer (opd R169) sequence is 5'CTTCTAGACCAATCGCACTG3' [33] with using1.5 μl of standard 1kb DNA ladder (Thermo Scientific, USA) were loaded in 1% agarose gel. Digital images were obtained for PCR products bands using Bio-Rad's Gel Doc XR+ system.…”
Section: Malathion Residual Analysis Using High-performance Liquid Ch...mentioning
confidence: 99%
“…Different species of Pseudomonas have been found to be an effective biodegrader of different organophophorus insecticides (Bano and Mussarrat, 2003;Lei et al, 2005;Madhuri and Rangaswamy, 2009;Malghani et al, 2009;Rani and Juwarkar, 2012). Iyer et al (2011) reported the biodegradation of phorate (Ortiz-Hernandez et al, 2003;Serdar et al, 1982). To date, only one Pseudomonas sp.…”
Section: Introductionmentioning
confidence: 95%